ECOURI ALE TRECUTULUI, CONTURÂND VIITORUL: EVOLUȚII ALE NARAȚIUNILOR STRATEGICE PROMOVATE DE VLADIMIR PUTIN ÎN DISCURSURILE DIN ADUNAREA FEDERALĂ - Andrei-Cristian MORARU (Intelligence și Cultura de Securitate)
The present study conducts a comprehensive content analysis of the presidential speeches delivered by Vladimir Putin at the Federal Assembly of the Russian Federation in the years 2021, 2022, and 2023. The research aims to identify the strategic narratives endorsed by the Russian government in these discourses, while also aiming to establish their evolution over time, comparing them with the national security objectives of the Russian Federation post-2021. The analysis demonstrates a marked shift in the foreign policy of Russia from a defensive and reactive stance in the year 2021 to a more assertive and proactive one in the speeches delivered by Putin in 2022 and 2023. Such discourses have been observed to emphasize the central role played by Russia in the global arena, while also strongly advocating for the pursuit of its national interests. Moreover, this study provides a significant contribution to the redefinition of the conceptual framework of strategic narratives, viewing them as a tool that is utilized by aggressor states to justify military actions, and more importantly, to establish a strong position in the international power dynamics. The findings of this study offer valuable insights into the strategic narratives that are promoted by the Russian government, and the evolution of such narratives over time. The research has critical implications for policymakers, scholars, and other individuals who are interested in understanding Russia's foreign policy priorities and its positioning on the global stage. The study underscores the significance of discursive strategies and the role that they play in shaping a country's foreign policy objectives, particularly in times of geopolitical tensions. Overall, this research constitutes a relevant contribution to the understanding of Russian foreign policy and the vital importance of strategic narratives in shaping such a policy.